Pervasive Haptics Science, Design, and Application - Kajimoto, Hiroyuki; Saga, Satoshi; Konyo, Masashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book examines the state of the art in diverse areas of haptics (touch)-related research, including the psychophysics and neurophysiology of haptics, development of haptics displays and sensors, and applications to a wide variety of fields such as industry, education, therapy, medicine, and welfare for the visually impaired. It also discusses the potential of future haptics interaction, such as haptics for emotional control and remote haptics communication. The book offers a valuable resource not only for haptics and human interface researchers, but also for developers and designers at manufacturing corporations and in the entertainment industries.
Psychophysical Dimensions of Material Perception and Methods to Specify Textural Space -- The Brain Network for Haptic Object Recognition -- Understanding force perception characteristics of a human and its applications -- Tactile Display Using the Micro-vibration of Shape-Memory Alloy Wires and its Application to Tactile Interaction Systems -- Electro-tactile Display: Principle and Hardware -- Solid Ultrasonics Tactile Displays -- Lateral-Force-Based Tactile Display -- Airborne Ultrasound Tactile Display -- Tactile sensing techniques that use intrinsic force sensors -- Reflection-Image-Based Tactile Sensor -- Thermal Displays and Sensors -- TECHTILE workshop for creating haptic content -- Computational Aesthetics: From Tactile Score to Sensory Language -- Haptic Aids for the Visually Impaired -- Toward the haptic interaction in daily life -- Haptic Interfaces that Induce Motion and Emotion -- Bidirectionality of Haptics -- Remote Transmission of Multiple Tactile Properties.
Keywords: Engineering; User interfaces (Computer systems).; Computational intelligence; Robotics; Automation; Biomedical engineering; Engineering; Robotics and Automation; Computational Intelligence; User Interfaces and Human Computer Interaction; Biomedical Engineering